2014
DOI: 10.1155/2014/292545
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Efficacy of Ectoine Nasal Spray in Patients with Allergic Rhinoconjunctivitis

Abstract: Objectives. The meta-analysis aims to investigate the efficacy of ectoine nasal spray and eye drops in the treatment of allergic rhinitis and rhinoconjunctivitis symptoms. Design and Methods. This meta-analysis is based on yet unpublished data of four studies. Both nasal and eye symptoms were documented in patient diary cards. All scales were transformed into a 4-point scale: 0 = no, 1 = mild, 2 = moderate, and 3 = severe symptoms. Each symptom was analysed individually in a meta-analysis of the area under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…In another NIS, ectoine-containing nasal spray and eye drops seemed to be a comparable alternative to traditional anti-inflammatory agents such as azelastine, cromoglycin and levocabastine for the treatment of AR [26,27]. Patients using ectoine nasal spray showed an improvement of about 32% in the symptoms of rhinorrhoea and 30% in nasal obstruction [26], as well as a reduction of 23% in the total nasal symptom score [27]. These results are in line with those demonstrated in this NIS.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In another NIS, ectoine-containing nasal spray and eye drops seemed to be a comparable alternative to traditional anti-inflammatory agents such as azelastine, cromoglycin and levocabastine for the treatment of AR [26,27]. Patients using ectoine nasal spray showed an improvement of about 32% in the symptoms of rhinorrhoea and 30% in nasal obstruction [26], as well as a reduction of 23% in the total nasal symptom score [27]. These results are in line with those demonstrated in this NIS.…”
Section: Discussionsupporting
confidence: 81%
“…In this NIS, we observed a statistically significant improvement in nasal symptoms of 27% in the ATANS group, demonstrating a similar effectiveness of ATANS to the aforementioned non-pharmacological treatment options. In another NIS, ectoine-containing nasal spray and eye drops seemed to be a comparable alternative to traditional anti-inflammatory agents such as azelastine, cromoglycin and levocabastine for the treatment of AR [26,27]. Patients using ectoine nasal spray showed an improvement of about 32% in the symptoms of rhinorrhoea and 30% in nasal obstruction [26], as well as a reduction of 23% in the total nasal symptom score [27].…”
Section: Discussionmentioning
confidence: 99%
“…All preparations studied have a high viscosity and are meant to entrap the pollen before they make contact with the nasal mucosa. Overall, the different products [4][5][6][7][8][9][10] were found to be effective in treating symptoms of AR, thus supporting the idea of a mechanical barrier against pollen. No study, however, examined the effects of these products in a controlled environment, nor their influence on biomarkers and cells of the allergic cascade.…”
Section: Introductionmentioning
confidence: 63%
“…These gels and ointments serve as a physical barrier and do not contain any pharmacologically active compounds. Some of these compositions have been investigated in clinical studies for efficacy in hay fever, for example, hypromellose [4][5][6], aliphatic long-chain hydrocarbons [7], ectoine [8], seawater gel [9], and xyloglucan [10]. All preparations studied have a high viscosity and are meant to entrap the pollen before they make contact with the nasal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that products containing ectoine may be a better alternative to other products, as they reduce ocular and nasal symptoms with no side effects (40)(41)(42). Promising effects such as reduction of nasal airway obstruction and crust formation were also observed in patients with rhinitis sicca anterior treated with nasal spray containing ectoine alone or in combination with dexpanthenol (43).…”
Section: Alleviation Of Inflammatory Reactionmentioning
confidence: 99%